IMMUNOGENICITY AND SAFETY OF A TRIVALENT SUBUNIT IMMUNOADJUVANT INFLUENZA VACCINE IN CHILDREN WITH TYPE 1 DIABETES: RESULTS OF A PROSPECTIVE COMPARATIVE STUDY - Аlla A. Tarasova; Еlena V. Кolbasina; Еlena F. Lukushkina; Yury G. Kuzmichev; Mikhail P. Kostinov ("Paediatrician" Publishers LLC, 2016)
Background: Children with type 1 diabetes (T1D) are at high risk for severe influenza. Objective. Our aim was to assess immunogenicity and safety of a trivalent subunit immunoadjuvant influenza vaccine in children with T1D. Methods. The prospective study carried out from September to November 2014 included children with T1D at the age from 3 to 17 years vaccinated against influenza by a trivalent subunit immunoadjuvant influenza vaccine and unvaccinated due to parental refusal. Anti-influenza virus antibodies were determined by passive hemagglutination reaction. Vaccine safety was assessed by a number of adverse events occurred within 6 days after its administration. Observation was carried out during 1 year after vaccination (to October-November 2015 inclusive). Results. Of 780 children with T1D followed-up by endocrinologists in Nizhny Novgorod region, the study included 94 children - 44 vaccinated and 50 unvaccinated matched by sex and age. As for influenza A/H1N1/California/07/09 virus strain, the seroprotection rate (antibody titre > 1:40) was 84%, seroconversion rate (4-fold increase in antibody titre) was 66%, seroconversion factor (average increase of the antibody titre and 95% confidence interval) was 20.6 (10.4-30.9), as for influenza A/H3N2/Texas/50/12 virus, it was 98%, 41%, and 9.9 (3.2-16.6), as for influenza B/Massachusetts/2/12 virus, it was 77%, 49%, and 7.7 (4.0-11.4), respectively. After 1 year, the conditionally protective antibody titres (> 1:40) to influenza A/H1N1/California/07/09 virus were in 32/43 (74%), to influenza A/H3N2/Texas/50/12 virus - in 38/43 (88%), to influenza B/Massachusetts/2/12 virus - in 25/43 (58%) vaccinated children, in unvaccinated ones - 23/49 (47%) 37/49 (76%), and 6/49 (12%), respectively. Mild local adverse events were observed in 5/44 (11%), general - in 1/44 (2%), intercurrent diseases - in 8/44 (18%) vaccinated children. Conclusion. Immunogenicity and safety of a trivalent subunit immunoadjuvant influenza vaccine in children with T1D have been confirmed.